Bank Syariah sebagai Mitra Distribusi pada Produk CWLS Ritel SWR003 Perspektif Maqashid Syariah - Setiyowati, Arin; Hartini, Dewi Sri (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze related to the role of Islamic banks as distribution partners in using Retail CWLS SWR003 in the perspective of maqashid sharia. This research was conducted using a qualitative research method, a literature study approach (Library Research). Data validity with source triangulation. The data analysis technique in this study is to use discourse analysis. The results of the study show that BSI as the nazhir partner and distribution partner of the SWR003 Retail CWLS program has implemented programs that are distributed to partners through Lazismu and BSM Ummah. Through the Village UMKM Program, SAUM, raising sheep, and Islamic boarding schools based UMKM. From a number of return fund distribution programs, the management of CWLS SWR003 funds in the perspective of Maqashid Syariah has fulfilled the concept of maqashid syariah which consists of dharuriyyah, hajiyyat, tasiniyah.